Effect of CRISP Method Training on ECG Diagnosis Skills of Prehospital Medical Services Personnel - Mustafa Ekici; Ömer Faruk Turan; İsmail Borazan; Fatih Mehmet Aksoy; Seher Yaman; Zeynep Kaplan (Eurasian Journal of Emergency Medicine)
Aim: In critical care settings where every minute is vital, early diagnosis and timely intervention are essential for preventing complications and improving patient outcomes. Prehospital and emergency department staff must be highly trained and capable of promptly applying medical knowledge, with electrocardiography (ECG) interpretation being a core competency. Materials and Methods: This randomized controlled trial included 176 participants divided into experimental and control groups. Baseline ECG analysis skills were assessed using a pretest. The control group received training using the classical method, while the experimental group was trained using the Cardiac Rhythm Identification for Simple People (CRISP) method. Post-training knowledge levels were evaluated through a post-test. Results: Statistically significant improvements were observed in the experimental group in the interpretation of normal sinus rhythm, supraventricular tachycardia, atrial fibrillation, and second-degree atrioventricular blocks (Mobitz type 1 and type 2). The CRISP method demonstrated superior effectiveness compared to the classical method in diagnosing these conditions. Conclusion: Both the classical and CRISP methods positively influenced participants’ ECG analysis skills. However, the CRISP method resulted in significantly better post-test performance and proved especially effective in identifying fatal arrhythmias. Importantly, the CRISP method was not less successful than the classical method in any aspect of ECG interpretation.